Il monitoraggio ambientale come “dispositivo” politico e “costrutto” socioculturale. Una proposta interpretativa e operativa a partire dalla città di Taranto - Enzo V. Alliegro (Archivio Antropologico Mediterraneo)
Territories affected by environmental anomalies have recently arouse an interest of anthropological disciplines. Anthropology aims at understanding expressive practices of malaise, defense actions, performances of resistance and contrast, ways of perception and risk processing, and so forth, of the people involved. This article, based on archival, journalistic, judicial and legislative sources and on the first results of a research led on the city of Taranto, proposes an analytical path of historical and political anthropology. As a result, it is put forward an interpretative proposal of applied anthropology aimed at overcoming the gap between local risk perception and public control and mitigation policies.